Antimicrobial peptides´ immune modulation role in intracellular bacterial infection - Duarte-Mata, Diana Ivonne; Salinas-Carmona, Mario César (Frontiers in Immunology, 2023)
Intracellular bacteria cause a wide range of diseases, and their intracellular lifestyle makes infections difficult to resolve. Furthermore, standard therapy antibiotics are often unable to eliminate the infection because they have poor cellular uptake and do not reach the concentrations needed to kill bacteria. In this context, antimicrobial peptides (AMPs) are a promising therapeutic approach. AMPs are short cationic peptides. They are essential components of the innate immune response and important candidates for therapy due to their bactericidal properties and ability to modulate host immune responses. AMPs control infections through their diverse immunomodulatory effects stimulating and/or boosting immune responses. This review focuses on AMPs described to treat intracellular bacterial infections and the known immune mechanisms they influence.